Genetic polymorphisms and immune cytokine profiles in the cellular pathogenesis of polycystic ovary syndrome among Iraqi women: Genetic and immune factors in Iraqi PCOS pathogenesis - Al-Taei, Orass Madhi Shaheed; Baqer Hussein Al-Harmooshee, Maather (Cellular and Molecular Biology, 2025)
Immune dysregulation and genetic polymorphisms are recognized as critical contributors to the pathogenesis of polycystic ovary syndrome (PCOS). The present study aimed to investigate the roles of specific cytokines and the CYP11A1 (rs4077582) polymorphism in Iraqi women diagnosed with PCOS. The current study included collecting samples from 100 women with PCOS and 100 healthy women as a control group. Clinical and laboratory tests were conducted at Diwaniyah General Hospital. The concentration of interferon-gamma, interleukin-2, interleukin-4 and interleukin-10 in the serum was determined utilizing the ELISA technique, while genetic CYP11A1(rs4077582) polymorphisms were determined using the PCR-RFLP technique. ELISA results demonstrated the concentration of interferon-gamma, interleukin-2 in FF in PCOS are significantly increased (123.8 ± 33.6, 45.77 ± 8.92 ng/ml respectively) compared with those in controls (23.5 ± 4.29, 7.31 ± 1.07 ng/ml respectively) while concentration of IL-4 and IL-10 reduced in patients (22.62 ± 6.24 and 5.81 ± 1.11 ng/ml respectively) compared to control (167.1 ± 18.62 and 37.54 ± 7.11ng/ml respectively). The results showed an increase in rate of mutant genotype CC and allele C in patients (34% and 64% respectively) compared to controls (12% and 25% respectively), while a decrease in the proportion of normal genotype TT and allele T in patients (6% and 36% respectively) compared with healthy subjects (62% and 75% respectively). immune function of IFN-γ, IL-2, IL-4 and IL-10 and CYP11A1(rs4077582) polymorphisms significantly associated with PCOS.